Effect of magnesium sulphate on duration and dose requirement of thiopental sodium anesthesia in dogs undergoing experimental enterotomy - HELAL, IBRAHIM; DAHRAWY, MOHAMED EL (The Indian Journal of Animal Sciences, 2012)
Adult mongrel dogs (15) of either sex, 1.8±0.7-year-old and weighing 15.56±0.06 kg (mean±SE) were used in the study to evaluate the effect of pre-and intra-operative administration of magnesium sulphate (MgSO4) on the duration and dose of thiopental sodium antesthesia undergoing enterotomy. All dogs were premedicated with intramuscular injection of chloropromazine hydrochloride 15 min prior to the injection of 2.5% thiopental sodium in group 1. In group 2, i/v administration of chloropromazine hydrochloride followed by a bolus of 50 mg/kg MgSO4 (10%) were used before injection of general anaesthesia. In group 3, the dogs received the same anesthetic protocol as in group 2 in addition to i/v infusion of MgSO4 (10%) @10 mg/kg/hr. Enterotomy model was created in all dogs and the mean operation time was 34 min. The results revealed that mean duration of anesthesia was significantly longer in groups 2 and 3 (43.40 and 57.60 min, respectively) as compared to group 1 (38.60 min). The mean total thiopental sodium dose in group 1 (32.10 mg/kg) was significantly greater than those of groups 2 and 3 (26.70 and 20.20 mg/kg respectively). It could be concluded that preoperative and intraoperative administration of MgSO4 prolong duration of anesthesia, decrease the total dose of thiopental sodium, and facilitate smooth recovery.